TP53 Codon 72 Polymorphism and the Risk of Colorectal Cancer in an Azerbaijani Population - Yagublu, Vugar; Bayramov, Bayram; Yuce, Melek; Aslanov, Hazi (Turkish Journal of Gastroenterology, 2022)
Background: We aimed to evaluate the association between the TP53 Arg72Pro gene polymorphism and risk of colorectal cancer in an Azerbaijani population. Methods: A total of 141 patients with colorectal cancer and 150 gender- and age-matched controls were involved in the study. The genotypes of the TP53 gene Arg72Pro polymorphism were detected by polymerase chain reaction-based restriction fragment length polymorphism analysis. Results: We found that the heterozygous genotypes Arg/Pro (odds ratio, 1.128; 95% CI, 0.657-1.937) and mutant Pro/Pro (odds ratio, 1.274; 95% CI, 0.648-2.504) were more frequent in colorectal cancer patients compared to healthy controls. The frequency of the mutant Pro allele (odds ratio, 1.122; 95% CI, 0.809-1.554) was revealed in 47.5% of colorectal cancer patients and in 44.7% of healthy controls. There was no association observed between TP53 Arg72Pro polymorphism and risk of colorectal cancer in an Azerbaijani population (P > .05). Conclusion: Our findings indicate a lack of relationship between TP53 Arg72Pro polymorphism and risk of colorectal cancer. Furthermore, we have found no statistical differences in the frequency of genotype and allele by sex, age, histological grade, tumor stage, smoking status, and alcohol consumption in this study.